KEDUDUKAN BARANG BUKTI TERHADAP PUTUSAN PENGADILAN DALAM PENYELESAIAN PERKARA PIDANA PEMBUNUHAN DI PENGADILAN NEGERI BARRU - Heri Tahir; Dian Eka Safitri (SUPREMASI: Jurnal Pemikiran, Penelitian Ilmu-ilmu Sosial, Hukum dan Pengajarannya, 2018)
This study aims to determine: 1). Procedure seizure of evidence in a criminal case of murder in Barru District Court and, 2). Status of the evidence against the court decision in settlement of a criminal case on the murder of Barru District Court. In this study the authors used qualitative research methods. Sources of data in this research is the primary data sources (informants) that District Court Judge Barru and secondary data sources (documents) that the case files. Data collection methods used were interviews and documentation. In this study, data validity checking technique used is triangulation techniques, data analysis techniques performed by descriptive analysis. The results of this study indicate that the procedure foreclosure carried out in accordance with the provisions of the legislation in force but in a state that is very necessary and urgent investigators can immediately seized evidence in a criminal case of murder and after the seizure investigator filed an application for approval of foreclosure to the Chairman of the Court Barru for obtain approval determination foreclosure. The pieces of evidence that directly confiscated by the investigator has a role in the process of proving to a court decision that consideration, and strengthen judges. Based on the above results it can be concluded that investigators can immediately seized evidence in a criminal case of murder, as confiscation in criminal cases of murder, including the circumstances that are very necessary and urgent that the investigator does not require a license foreclosures in advance of the Chairman of the Court Barru as stipulated in the procedure foreclosure, the investigator shall immediately report to the Chairman of the Court Barru after a foreclosure, in order to obtain approval of the determination letter seizure of evidence from the Chairman of the Court Barru. Position of evidence in a criminal case of murder in Barru District Court, is a belief that strengthen consideration for the judge, but does not specify the court decision / verdict against the defendant.